Scrotal displacement of the urinary bladder in a pig - Tan, H. S.; Chooi, Kum Fai; A. Azizi, Saleha (Persatuan Doktor Veterinar Malaysia, 1982)
A case of inguino-scrotal hernia in a nine-month-old castrated Landracex large white pig incolving the unirary is described. The condition was associated with ventral retroflexion of the bladder resulting in bilateral hydronephrosis and hydroureter